Program for international student assessment-based analysis for Javanese test - Venny Indria Ekowati; Endang Nurhayati; Suwarna Suwarna; Ines Ika Saputri (Institute of Advanced Engineering and Science, 2023)
This study aimed to analyze the test items of Javanese for junior high school in Special Region of Yogyakarta (DIY) using Program for International Student Assessment (PISA) literacy parameters. It was qualitative descriptive research employing content analysis methods. The instruments used were test items of PISA and Javanese reading literacy. The data collected was primary data in the forms of words, phrases, sentences, paragraphs, and discourses. The purposive sampling method was used to choose the research subjects. Data were analyzed using content analysis methods. The data collection was conducted through detailed documentation on test items of PISA reading literacy published by the Organization for Economic Co-operation and Development (OECD) and Curriculum 2013 Javanese reading test items for junior high school obtained from final examinations of four regions and one city in DIY. The semantic validity was used in this study. The results of the data analysis showed that out of 25 characteristics of PISA parameters of test items, there were only 13 (52%) characteristics a lied in test items of Javanese for junior high school in DIY, while the rest (48%) was not found in the Javanese test items. Based on these findings, it is expected that teachers can develop test items for Javanese reading literacy with higher thinking ability levels.